Species and Distribution of Invasive Plants in Kaeng Krachan Forest Complex : Case of Thai Prachan National Park, Ratchaburi Province - Withayawongruchi, Chainarong; Poopath, Manop; Maneeanakekul, Payak (STOU Journal of Agriculture (Online), 2019)
The study on species and distribution of invasive plants in Kaeng Krachan Forest Complex: case of Thai Prachan National Park, Ratchaburi Province, aims to determine the number of invasive species, quantity and distribution of exotic plants in Thai Prachan National Park. There were 13 study sites comprising service area, service area the Thai Prachan reservoir, agricultural area around the camping ground, Thai Prachan reservoir area, exotic forest plantation, Thai Prachan river area, native forest plantations, nature trails along the Thai Prachan reservoir, mixed deciduous forest around agricultural area, mixed deciduous forest around exotic forest plantation, mixed deciduous forest around native forest plantations, mixed deciduous forest around service area and mixed deciduous forest around Thai Prachan reservoir service area. Six hundred and thirty nine plots of 1 × 1 m were established. Invasive species were classified using a priority indices criteria and the value of prioritized indices. All Importance Value Index of invasive species were documented and focused on their distribution. One hundred and thirty exotic species were found and divided in to 48 invasive species and 82 non-invasive species. Ten major invasive plants: Chromoleana odoratum, Pennisetum polystachyon, Praxelis clematidea, Wedelia trilobata, Aeschynomene americana, Panicum maximum, Leucaena leucacephala, Mimosa pudica, Altemanthera dentate and Acmella oleracea were found. The areas with highest percentage of exotic species were service area (35 species), recreation zone (23 species) and agriculture zone (18 species), respectively. The forest closed to recreation zone had the lowest percentage with one species.